Women’s empowerment and energy access: Insights from India, Nepal, and Pakistan - Alvi, Muzna; Sufian, Farha; Ringler, Claudia; Singh, Tushar; Beniwal, Ezaboo; Raja, Sehrish (CGIAR, 2023)
Gendered inequities in access to and use of energy sources and technologies affect all five impact areas that CGIAR is contributing to: poverty alleviation, food security and nutrition, climate action, environmental health, and inclusion. This policy note identifies indicators that reflect women’s and men’s agency in the context of energy use and develops a first version of the Women’s Empowerment in Energy Index (WEEI) to measure changes in women’s agency over time.